Kendala Pengembangan Ternak Kerbau di Kecamatan Sijunjung Kabupaten Sijunjung - Taufik, Taufik; Elisia, Rini; Maiyontoni, Maiyontoni; Komala, Refika (Fakultas Pertanian Universitas Muara Bungo, 2024)
This research aims to determine the distribution of the buffalo livestock population in Sijunjung District, to determine the obstacles in developing buffalo livestock in Sijunjung District and to determine the role of the government in developing buffalo livestock in Sijunjung District. This research was carried out in Sijunjung District, Sijunjung Regency, West Sumatra Province. The population in this study was all 130 buffalo breeders in Sijunjung District. This research uses a census method, by collecting information from all buffalo breeders in Sijunjung District, using a structured questionnaire as a data collection tool to obtain specific information. The data used is primary and secondary data. Data analysis used to measure obstacles to buffalo livestock development is descriptive statistical analysis in the form of tabulations (percentages and numbers). The parameters observed in this research were the distribution of the buffalo livestock population, the human resources of the breeders and maintenance management. Based on the research results, it can be concluded that the distribution of the buffalo population in Sijunjung District, Sijunjung Regency is based on the gender of 185 male buffaloes and 631 female buffaloes. Meanwhile, based on growth rate, there are 374 calf buffaloes, 301 mother buffaloes, 96 single buffaloes and 45 heifers. The total number of buffalo livestock in Sijunjung District, Sijunjung Regency is 816 heads and the obstacles in controlling buffalo livestock in Sijunjung District, Sijunjung Regency are the availability of feed due to land conversion and climate influences, disease control which is not prioritized by breeders and the resilience of the government is obstacles to the development of buffalo livestock, government support is really needed by farmers, such as free treatment and vaccines